Understanding the Impact of Sheep Digestion on Seed Germination in the Cold Desert Annual Diptychocarpus strictus with Emphasis on Fruit and Seed Heteromorphism - Xuheng Zhao; Yixiang Wang; Fangfang Cao; Xuzhe Wang; Fanfan Zhang; Sumera Anwar; Zhihua Sun; Hongsu He (Life, 2024)
This study aimed to investigate the morphological characteristics of fruits and seeds from Diptychocarpus strictus, a plant species inhabiting the cold desert pastoral area of China. Furthermore, this study sought to evaluate the germination potential of these seeds following digestion by sheep. This study employed the sheep rumen fistula method to simulate rumen digestion at various time intervals. Subsequently, an in vitro simulation method was utilized to simulate true gastric and intestinal digestion after rumen digestion. Paper germination tests were then conducted to assess the impact of the digestive process on the heteromorphic seed morphology and germination. During rumen digestion, the seeds were protected by wide wings. The results revealed a highly significant negative correlation (p < 0.01) between seed wing length and digestion time. Post-rumen digestion, variations in the germination rate among seeds from fruits at different locations were observed. Indicators, such as germination rate, exhibited a highly significant negative correlation with rumen digestion time (p < 0.01). In vitro simulated digestion tests demonstrated that Diptychocarpus strictus seeds retained their ability to germinate even after complete digestion within the livestock’s digestive tract. The polymorphic nature of Diptychocarpus strictus seeds, coupled with their capacity to survive and germinate through the digestive tract, facilitates the spread of these seeds. This finding has implications for mitigating desert grassland degradation and promoting sustainable ecological development.